Vitamin D : new perspectives in drawing. (London : Phaidon, 2005)
Alvarez, D-L ; Alÿs, Francis ; Aoki, Ryoko ; Arima, Kaoru ; Bächli, Silvia ; Banhart, Devendra ; Barriball, Anna ; Bool, Shannon ; Borremans, Michaël ; Bowers, Andrea ; Bransford, Jesse ; Bryce, Fernando ; Cai Guo-Qiang ; Caivano, Ernesto ; Chaves, Raimond ; Cinto, Sandra ; Crotty, Russell ; Cuoghi, Roberto ; Currin, John ; Cutler, Amy ; Davis, Jeff ; Dean, Tacita ; Donnelly, Trisha ; Dr. Lakra ; Dumas, Marlene ; Durant, Sam ; Dzama, Marcel ; Erdener, Mehmed ; Evans, Simon ; Faithfull, Simon ; Finch, Spencer ; Fischer, Urs ; Flexner, Roland ; Gallagher, Ellen ; Greene, Matt ; Grigely, Joseph ; Gudmundsdottir, Anna Sigmond ; Guzman, Daniel ; Hammwöhner, Sebastian ; Hancock, Trenton Doyle ; Hegardt, Björn ; Herrera, Arturo ; Hoki, Nobuya ; Holstad, Christian ; Huang Yong Ping ; Hughes, Dean ; James, Gareth ; Johanson, Chris ; Kartscher, Kerstin ; Kentridge, William ; Khedoori, Toba ; Landy, Michael ; Lanzarini, Ricardo ; Little, Graham ; Lombardi, Mark ; Los Carpinteros ; Lukosaitis, Mindaugas ; Maggi, Marco ; Magnotta, Frank ; Manders, Mark ; Masnyj, Yuri ; McGill, Dominic ; Mehretu, Julie ; Moriceau, Jean-François ; Mrzyk, Petra ; Müller, Claudia & Julia ; Muller, Dave ; Muniz, Vik ; Musgrave, David ; Mutu, Wangechi ; Nara, Yoshitomo ; Noble, Paul ; Nordström, Jockum ; Novoa, Glexis ; O'Neil, Robyn ; Ondák, Roman ; Orozco, Gabriel ; Pepperstein, Pavel ; Peri, Peter ; Perjovschi, Dan ; Pettibon, Raymond ; Peyton, Elizabeth ; Piene, Chloe ; Renes, Fernando ; Rhode, Robin ; Richardson, Frances ; Ritchie, Matthew ; Schatz, Silke ; Schneider, Anne-Marie ; Serse ; Shearer, Steven ; Shrigley, David ; Shubuck, Simone ; Siena, James ; Sikander, Shahzia ; Skaer, Lucy ; Slama, Torsten ; Smith, Josh ; Smith, Zak ; Solakov, Nedko ; Tompkins, Hayley ; etc.
boek